Reklamasi Tambang Berkeadilan dan Mensejahterakan - Pambudi, Priyaji Agung; Utomo, Suyud Warno; Soelarno, Soemarno Witoro; Takarina, Noverita Dian (Jurnal Mineral, Energi dan Lingkungan, 2023)
The mining industry has an important contribution to the economy and regional growth, but it also has the risk of environmental disturbance, so it is required to carry out reclamation. A special strategy is needed for the success of reclamation can improve the quality of life of the community and other organisms. The purpose of this research is to examine successful mining reclamation methods that can be implemented. This study uses a qualitative approach through social observation, questionnaires, in-depth interviews, and a literature review. Reclamation by PT. X consists of programs for the preparation, planning, implementation and management of reclamation areas. At the preparation stage PT. X conducts public consultations to listen to suggestions, opinions and responses from local communities, especially land owners who are rent. PT. X applies the participatory-accommodative principle. This strategy puts forward a bottom-up mechanism, namely the local landowners provide advice to PT. X related to the type and implementation of reclamation and PT. X conducts verification as well as careful and in-depth studies of technical implementation. Reclamation needs to be managed by providing an enclave zone that acts as a center for mining environmental protection. The area of the enclave zone should ideally be determined based on consideration of the area of the IUP, ecosystem typology, diversity, evenness and distribution of flora and fauna, as well as total carbon emissions. Just and prosperous reclamation is carried out by considering the existence and proper allocation of space for abiotic and biotic components including sources of livelihood for local communities.